Accounting knowledge, entrepreneurial spirit and capital accessibility as business performance improvement strategies - Tuntun Salamatun Zen, Umi Zuraida, Asep Darmansyah, Evy Rachmawati Chaldun, (Opción, 2019)
This research reveals the strategy that can improve the business performance of Indonesian footwear industry and the model that can improve the accessibility to the capital resources. The study used descriptive methods, and the unit of analysis was the footwear industry in Bandung. The results show that strategies to improve the performance of the footwear industry with the expansion of business negotiations, enhancement of marketing capabilities, and financial management and reporting capabilities. In conclusion, increasing the accessibility of capital is done by simplifying the loan procedures, developing the profit sharing financial system, and expanding the source of funds from individuals.